Effectiveness Of Action Observation Therapy In Improving Apraxia And Functional Outcomes In Post-Stroke Patients: A Systematic Review - Habib Laksmana Prima Prima; Rizqiana Arum Sari; Tegar Harputra Raya; Elien Wihestin (International Journal of Health Engineering and Technology, 2026)
Apraxia is a higher-order motor disorder commonly observed after stroke, characterized by impaired motor planning despite preserved motor strength. Conventional rehabilitation often fails to adequately address this deficit. Action observation therapy (AOT), based on the mirror neuron system, has emerged as a potential intervention targeting motor planning mechanisms. To evaluate the effectiveness of action observation therapy in improving apraxia severity and functional performance in post-stroke patients. A systematic review was conducted following PRISMA guidelines. Literature searches were performed in PubMed, Cochrane Library, and ScienceDirect. Randomized controlled trials evaluating AOT in stroke patients were included. Due to heterogeneity in outcome measures, a qualitative synthesis was performed. Five studies were included. Two studies directly assessed apraxia and demonstrated significant improvements in praxis-related outcomes following AOT. All studies reported improved motor function and functional performance, with greater gains observed in AOT groups compared to conventional rehabilitation. However, findings related to manual dexterity were inconsistent across studies. AOT may enhance motor recovery by facilitating motor planning through activation of shared neural pathways involved in action observation and execution. While evidence supports its benefit in both apraxia-specific and general stroke populations, variability in study design and outcomes limits definitive conclusions.Action observation therapy shows potential in improving apraxia and functional outcomes after stroke, but further high-quality studies are needed to confirm its effectiveness.